Factorizations for q-Pascal matrices of two variables - Ernst Thomas (Special Matrices, 2015)
In this second article on q-Pascal matrices, we show how the previous factorizations by the summation matrices and the so-called q-unit matrices extend in a natural way to produce q-analogues of Pascal matrices of two variables by Z. Zhang and M. Liu as follows